Evaluasi Pemanfaatan Institutional Repository (IR) dalam Penyusunan Karya Ilmiah Tugas Akhir Mahasiswa: Studi Kasus PTKIN di Jawa Timur - Ummi Rodliyah; Habib Habib (IJAL (Indonesian Journal of Academic Librarianship), 2019)
This study wants to reveal the utilization of the East Java State Islamic Religious College (PTKIN) repository in the preparation of student final assignments (theses and dissertations). The researcher used a quantitative descriptive approach in the form of a case study, through the documentary method evaluating the statistical menu in each repository for the data of repository utilization. While the repository role data for the preparation of the final assignment, researchers took samples with proporsive sampling techniques based on certain criteria, which is intended for those who are preparing final assignments and completing their studies in 2018. The results of this study is the level of utilization of the Institutional repository of East Java PTKIN is generally good. The UINSA repository which has 18,000 titles, is the repository with the highest number of accesses which is 5,722,154 accesses or 312 times the number of titles. While the UINMA Repository which separates the management of lecturers' work with the students’ in different repositories is in the 2nd place after UINSA. The smallest access of repository is in IAIN Ponorogo. The role of the repository in the preparation of the final assignments can be seen in 2 (two) forms, that are access and quoting. Access to the repository in order to find out research topics related to the field of research being studied by the respondent and previous research and the results. While in terms of citing reference sources in the preparation of the final assignment, there were 60% of respondents claiming to have quoted more than 3 times from the repository. Whereas from the level of popularity, the UINSA repository was at the top, and was accessed by respondents in all East Java PTKIN.